Influence of Polymer Superplasticizers Usage on Workability and Compressive Strength of 30 MPa and 40 MPa Concrete - Iranata, Data; Suswanto, Budi; Septiarsilia, Yanisfa (Jurnal IPTEK, 2024)
The advancement of technology has provided various alternatives to address limitations in concrete construction. One effective method for enhancing the quality of concrete is by introducing additional materials, known as admixtures, during the concrete production phase. One such type of admixture that can significantly improve concrete quality is superplasticizer. The primary principle behind the use of superplasticizer is to create a repelling force between cement particles to prevent clumping, which can lead to the formation of air voids in the concrete. This, in turn, can reduce the strength or quality of the concrete. In this research, the focus will be on the use of concrete admixtures, specifically superplasticizer, to enhance concrete workability. One product of superplasticizer is Sika Viscocrete 3115 N, which will be used in this study. Superplasticizers like Sika Viscocrete 3115 N play a crucial role in improving the flow and workability of concrete mixes, making them easier to handle and place during construction. This leads to more efficient and high-quality concrete structures. The target compressive strengths are 30 MPa and 40 MPa with variations in the percentage of superplasticizer admixture usage at 0%, 0.25%, 0.5%, and 0.75%. The testing methods used to determine the workability value are the slump test and the slump flow test, while the compressive strength test is conducted using a compression testing machine at the Advanced Concrete Materials and Computational Mechanics Laboratory, Department of Civil Engineering, ITS. The study concludes that the addition of superplasticizer can enhance the workability of concrete but cannot optimally increase compressive strength. Additionally, different planned compressive strengths with the same percentage variation exhibit different trends. The addition of 0.25%-0.5% superplasticizer in both planned strengths still yields compressive strength above the planned levels, despite the decrease.